PERANAN PETERNAKAN KAMBING DALAM EKONOMI PETANI DI LERENG GUNUNG MERAPI âStudi Kasus Di Desa Talun, Kecamatan Kemalang, Kabupaten Klaten, Jawa Tengahâ - , MUHAMMAD FATHUL FARIKH FAUZY ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper tried to understanding the roles of livestock (goats) in peasant society, in Mount Merapi. Main idea of this paper came from KKN-PPM UGM, 2012. The livestock (goats) have significant role for poor peasant to improving their economic. Peasant society like in Mount Merapi, they live with disaster potential from Mount Merapi. For this reason, livestock especially goats can be functioned as goods or wealthy. The people used for wedding ceremony, selamatan (worship ritual) and recover household economic after natural disaster from Merapi or failed crops. The result of this research for peasant is goats and cows have significant role, besides from crops products. In this case, livestock for peasant like goats and cows, used continuing, every time. Local peasant tried to herding the cows and goats with joint venture system or penggaduhan. The local system was helping rich peasant to expand their business and also poor peasant to looking for minimum income. With this system, poor peasant possess more opportunity, to improving economic, herding goats and also cows, like rich peasant.